EL ENSAYO ACADÉMICO COMO UNA ESTRATEGIA DE APRENDIZAJE PARA LA DIVULGACIÓN DEL CONOCIMIENTO DE BIOLOGÍA CELULAR CON LOS ESTUDIANTES DE SEGUNDO SEMESTRE DE LA CARRERA DE PEDAGOGÍA DE LA QUÍMICA Y BIOLOGÍA, PERÍODO OCTUBRE 2019 ABRIL 2020 - Sánchez Calderón, Jhoselyne Matilde (2020)
The research took place at the National University of Chimborazo, in the Faculty of Humanities Education and Technologies, Career of Experimental Sciences Pedagogy in Chemistry and Biology, with second-semester students, in the subject of Cell Biology. The problem was that the students do not give importance to the academic essay, as a learning strategy, to improve the dissemination of knowledge. The objective is to describe the significance of the academic essay as a learning strategy, to enhance dissemination of knowledge of Cell Biology with second-semester students of the Chemistry and Biology Pedagogy Career, the period October 2019 to April 2020. The method applied in the investigation was analysis-synthesis and inductive-deductive method to collect data, for the scientific investigation of the theoretical framework, the type of bibliographic and field research, which gave us the necessary information to do the work, the applied technique was the survey to verify the existing problem of the investigation. The result that encompasses the research was that the academic essay should be applied as a learning strategy in academic training, to the necessary alternative 83%, which showed that this tool is essential to improve the dissemination of knowledge in Biology Mobile. The work concluded with the description of the importance, that the academic essays have in the academic formation, it is an effective strategy to improve learning and as an instrument of dissemination of knowledge, this because the students must encourage comprehensive reading and develop a critical thinking.